Nonsurgical management of a large periapical lesion associated with an immature tooth displaying external inflammatory resorption - Fernandes, Marina (J Conserv Dent, 2015)
Immature nonvital teeth can often be associated with periapical lesions. Presence of external inflammatory resorption can complicate the treatment plan. A 21-year-old female patient presented with a large periapical lesion in relation to teeth 11 and 12. Tooth 11 was an immature tooth undergoing external inflammatory resorption. Aspiration through the root canal was carried out to evacuate the purulent fluid in the periapical lesion. Triple antibiotic paste was then placed as an intracanal medicament for a period of 2 weeks, followed by calcium hydroxide therapy for a period of 2 months. Mineral trioxide aggregate was then placed as an apical barrier to a thickness of about 4 mm. Obturation of the remainder of the canal space was done after 48 h. Complete periapical healing was evident after 1 year and 6 months. Nonsurgical healing of a large periapical lesion associated with an immature tooth displaying external inflammatory resorption can be successfully achieved.